Strategi Bauran Pemasaran Pada UMKM Dalam Perspektif Manajemen Pemasaran Syari’ah - purwanti, Neli (Coopetition : Jurnal Ilmiah Manajemen, 2025)
This study examines the implementation of marketing mix strategies in Micro, Small, and Medium Enterprises (MSMEs) from a sharia marketing management perspective. The study focuses on integrating Islamic values ​​into product, price, place, and promotion aspects so that marketing activities are not only aimed at commercial profit but also based on sharia principles such as honesty, fairness, transparency, and blessings. This research method uses a qualitative approach based on literature review. The results of this study indicate that MSME products must meet the criteria of halal and thayyib products with appropriate innovation, fair prices without usury or fraudulent practices, inclusive and accessible places and distribution, and honest and educational promotions. Implementing this strategy increases the trust and loyalty of Muslim consumers and supports the ethical sustainability of MSME businesses, while simultaneously empowering the ummah's economy in the digital and global era. The findings of this study emphasize the importance of synergy between spiritual values ​​and business objectives in managing sharia-based MSME marketing. Keywords: Strategy Implementation, Marketing Mix, Sharia Marketing Management.